PEDAGOGICAL ASPECTS OF KINDERGARTEN TEACHERS IN PRE-SCHOOL INSTITUTIONS - Duško Bjelica; Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
A poll procedure has been done at sample of 102 kindergarten teachers with Bachelor degree attending Specialist studies at Department of Pre-School Education of the Faculty of Philosophy in Niksic, and the aim of the poll was to determine the examinees' opinions on games organizations in pre-school institutions, from all towns of Montenegro. All of the questioned teachers were employed during the poll or they had already had working experience. The poll was based on the 14 questions ques¬tionnaire, especially made for this purpose in which the questions were classified in groups in order to determine 4 aspects that are important for successful organization of games. The first group of the questions regards choice of the games to be played; the second group relates to space choice for the game, as the third group of the questions refers to the way of making groups of children during preparation. The fourth group of the questions regards making cooperation and tolerance among the children during the games' realization. This poll is a part of the research done at the Faculty of Sports and Physical Education in Niksic with the aim to get directions for improving teaching and expert work in pre-school institutions through monitoring and insight into opinions of Specialist studies' students.